Formulation and Evaluation of Herbal Topical Gel Containing Leaves Extract of Andrographis paniculata - Samuel, Aney Joice; Mulla, Nida (Journal of Drug Delivery and Therapeutics, 2020)
Objective: The present study has been undertaken with the aim to formulate and evaluate the gel contaning leaf extract of Andrographis Paniculata.Methodology and results: The formulation was designed by using alcoholic extract of leaves of Andrographis paniculata.The gel was prepared by using  carbapol 934, triethanolamine, propylene glycol, methyl paraben, propyl paraben and required amount of distilled water. The prepared gel was evaluated for physical appearance, pH, spread ability, viscosity, extrudability, albumin denaturation assay and stability.Conclusion: Carbopol gels with dried leaves extract of Andrographis paniculata could be prepared successfully.Key words: Topical gel,Kalmegh, Spreadability, Albumin denaturation